Thermal boundary conductance of transition metals on diamond. Issue 2 (April 2012) - Monachon, Christian; Weber, Ludger
Abstract : An experimental process that was used to obtain a direct measurement of thermal boundary conductance (TBC) between a diamond substrate and several transition metals, deposited by sputtering, is described. Using time-domain thermoreflectance (TDTR), the critical parameters, for a proper interpretation of the results, are evaluated to be the laser spot size and the thickness of the metallic thin films. Values of TBC between Cu, Cr, Nb, Mo, W and diamond are presented and vary between 30 and 280 MW/m 2 /K. The adhesion of the layer to the substrate is seen to be critical to obtain a high TBC. Annealing in vacuum at temperatures up to 600°C does not significantly seem to change the results obtained. When diamond surface is oxygen plasma treated for better adhesion, the TBC between Cr and diamond is measured to be 325 MW/m 2 /K. This represents an 11-fold increase compared to untreated diamond.